Specific fibroblast subpopulations and neuronal structures provide local sources of Vegfc-processing components during zebrafish lymphangiogenesis - Guangxia Wang (Nature Portfolio, 2020)
How and where VEGF-C is processed in lymphangiogenesis is unclear. Here, the authors show that development of the zebrafish lymphatic system is locally restricted by Vegfc maturation causing lymphatic sprouting in certain regions, which is regulated by the metalloproteases ADAMTS3 and ADAMTS14.